Os impasses da sublimação: articulações entre psicanálise e estética - Neves, Sergio Luiz dos Santos (2020)
Submitted by Boris Flegr (boris@uerj.br) on 2020-08-02T16:52:27Z No. of bitstreams: 1 Sergio Luiz dos Santos Neves-Tese.pdf: 917472 bytes, checksum: 0fb932745c402c4734bc946a00b3b279 (MD5)